Interventional bronchoscopy - Criner, Gerard J.; Eberhardt, Ralf; Fernandez-Bussy, Sebastian; Gompelmann, Daniela; Maldonado, Fabien; Patel, Neal; Shah, Pallav L.; Slebos, Dirk-Jan; Valipour, Arschang; Wahidi, Momen M.; Weir, Mark; Herth, Felix (American journal of respiratory and critical care medicine, 2020)
For over 150 years, bronchoscopy, especially flexible bronchoscopy, has been a mainstay for airway inspection, the diagnosis of airway lesions, therapeutic aspiration of airway secretions, and transbronchial biopsy to diagnose parenchymal lung disorders. Its utility for the diagnosis of peripheral pulmonary nodules and therapeutic treatments besides aspiration of airway secretions, however, has been limited. Challenges to the wider use of flexible bronchoscopy have included difficulty in navigating to the lung periphery, the avoidance of vasculature structures when performing diagnostic biopsies, and the ability to biopsy a lesion under direct visualization. The last 10-15 years have seen major advances in thoracic imaging, navigational platforms to direct the bronchoscopist to lung lesions, and the ability to visualize lesions during biopsy. Moreover, multiple new techniques have either become recently available or are currently being investigated to treat a broad range of airway and lung parenchymal diseases, such as asthma, emphysema, and chronic bronchitis, or to alleviate recurrent exacerbations. New bronchoscopic therapies are also being investigated to not only diagnose, but possibly treat, malignant peripheral lung nodules. As a result, flexible bronchoscopy is now able to provide a new and expanding armamentarium of diagnostic and therapeutic tools to treat patients with a variety of lung diseases. This State-of-the-Art review succinctly reviews these techniques and provides clinicians an organized approach to their role in the diagnosis and treatment of a range of lung diseases.